Social Policy in the Protection of Street Children in Indonesia - Nunung Nurwati; Muhammad Fedryansyah; Willya Achmad (Universitas Sultan Ageng Tirtayasa, 2022)
Indonesia is one of the countries that have the most street children among developing countries. This study aims to determine the methods in the social policy of child protection among street children in Indonesia. This study uses a qualitative approach with a literature review method including 15 full-text journals. Publications are screened, analyzed and reviewed for research. Data sources consist of government and private publications. The results showed 67,000 street children, or about 10.51 percent of children with social welfare problems. Most street children abuse drugs and alcohol. Poverty and peer pressure bring children to the streets. Drug and alcohol abuse causes respiratory, digestive, mouth, face, and heart problems. Drug abuse causes HIV/AIDS, STIs, violence, and crime. Indonesia adopted the Convention on the Rights of the Child and established Integrated Street Children Programs in significant cities. Health, education, housing, nutrition, and the rights of street children are addressed. The Medical and Public Health Model is used for the prevention of drug abuse. From this research, it is also concluded that to avoid street children in Indonesia, and we need an approach to empowerment, employment, equality, and culture.